Music in mood regulation in adolescence : an initial exploration of the Singapore context - Chin, Ngeet (2016)
The use of music in mood regulation for adolescents is an important topic in the field of Music and Psychology. However, studies on this specific but important topic have been few and limited. The small number of studies that have been done have used mainly participants from Finland and Europe. The use of music in mood regulation for adolescents in other cultures like in Asia has not been explored. There also appears to be a lack of focus and understanding in the country of Singapore regarding the use of music for more therapeutic purposes like for mood regulation. This study seeks to be a pilot in presenting and understanding the use of music in mood regulation by adolescents in Singapore, a country made up mainly of people of Asian cultural lineage. Findings may fill in the gap in the understanding of the use of music and mood regulation in adolescence beyond a Western cultural context, and at the same time, serve as an initial data and proposal for expanding the use of music in therapeutic ways in Singapore. A self-administered questionnaire, consisting of both a quantitative survey using the Music in Mood Regulation (MMR) scale as well as open-ended interview questions, was distributed online. 60 responses were collected from adolescents in Singapore. Data from the open-ended questions were content-analysed and numerical information were gathered. Data collected from the MMR scale were statistically analysed. Results show that Singaporean adolescents do use music for mood regulation, and an overview of when, what, and why music is used is presented. It was also found that Singaporean adolescents use all regulatory strategies of music, and this was similar across age, gender and ethnic groups. Comparisons of findings from the current Singaporean study with what has been previously found of Finnish adolescents suggested that the basic process for the use of music in mood regulation is similar between Asian and Western cultures, but some differences relating to cultural contexts were also seen. Applications and limitations of the study are also discussed.